Impact of Age, Comorbidities and Complications in COVID-19 Patients with Acute Respiratory Distress Syndrome on Invasive Mechanical Ventilation. An Observational Multicenter Study - Francisco E. Arancibia; Gustavo Zabert; Fernando Rainieri; Javier Osatnik; Mariano Esperatti; Claudia Sepúlveda; Ignacio Zabert; Daniel Ivulich; Carlos M. Luna (Respirar, 2024)
Objectives: Millions of patients with COVID-19 were admitted to intensive care worldwide, half developed acute respiratory distress syndrome (ARDS) and received invasive mechanical ventilation (IMV), with a mortality of 50%. We analyzed how age, comorbidities and complications in patients with COVID-19 and ARDS who received IMV were associated with the risk of dying during their hospitalization.